Insomnia and other adult sleep problems - Stores, Gregory (Facts (Oxford, England), 2009)
Many adults suffer from disturbed sleep. There are many possible causes for sleep problems, some psychological, others physical, and these can lead to unneccessary problems with health and well-being. Comprehensive but easily understood, this book will help you to identify and explain problems leading to appropriate advice or treatment as necessary. It provide explanation of the possible causes, significance, and treatment of insomnia, excessive sleepiness, and disturbed behaviourat night. Throughout the book, advice is provided to help adults to sleep effectively with extra coverage included for those at particular risk of sleep problems, such as shift workers and parents of young children. Case studies are included to illustrate how adults with various sleep disorders have been correctly diagnosed and treated, and 'Myths vs. Facts' boxes help sort the valuable information from the misleading. Insomnia and Other Adult Sleep Problems: The Facts will be an invaluable resource for anyone with a sleep problem, their families, and the numerous health professionals who come into contact with those who suffer from sleep problems.